Kesulitan Guru dalam Mengembangkan Kemampuan Berpikir Kritis Siswa Kelas XI SMA melalui Penulisan Karya Ilmiah - Athi’ Firliya Rusdiyana; Didin Widyartono; Febri Taufiqurrahman (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This research aims to explore the challenges encountered by teachers in fostering the critical thinking skills of 11th-grade students at an Islamic senior high school (MA) through scientific writing activities. The study evaluates students' critical thinking based on five of the six indicators proposed by Facione: interpretation, analysis, evaluation, inference, and explanation. A qualitative method was applied, with the main data source consisting of excerpts from students’ scientific papers. Data collection involved observations and interviews. The analysis followed Facione’s critical thinking framework. The research was conducted at MA Al-Ittihad Belung, Poncokusumo, with data gathered from: (1) subject teachers, (2) students' scientific writings, and (3) 11th-grade students with varying levels of inference skills. The central objective of this study is to uncover the difficulties teachers face when guiding students to develop critical thinking through scientific writing. Findings reveal that many students still face obstacles in several aspects of critical thinking, such as correctly interpreting information, logically analyzing and evaluating arguments, and formulating sound conclusions. This study is considered important because writing scientific articles at the senior high school level is a complex process that demands structured guidance in critical thinking, support that is often lacking in classroom practices.